Larvicidal activity of Ocimum campechianum, Ocotea quixos and Piper aduncum essential oils against Aedes aegypti - Scalvenzi, Laura (Parasite, 2019)
Aedes aegypti, the main arbovirus vector of the Yellow fever, Dengue, Chikungunya and Zika viruses, is widely distributed in tropical and subtropical areas throughout the world. Preventive control efforts have been implemented worldwide aimed at reducing its impact on human health. The recent reduction of chemicals available for vector control due to their negative impact on the environment and human health and the increase in mosquito resistance to insecticides have driven the research community to identify and evaluate sustainable alternatives to synthetic insecticides. In this study, the potential larvicidal effect of essential oils extracted from Ocimum campechianum, Ocotea quixos and Piper aduncum were tested in vitro. GC and GC–MS analyses showed that the main compounds were eugenol (18%), 1,8-cineole (39%) and dillapiole (48%), respectively. Susceptibility to essential oils was measured according to the WHO protocol. After 24 h, the mean percentage mortality ranged from 2.7 to 100% for P. aduncum, from 2.2 to 100% for O. campechianum, and from 2.9 to 100% for O. quixos. The highest potential was displayed by P. aduncum, followed by O. campechianum and O. quixos, with LC(50) values of 25.7, 69.3 and 75.5 ppm, respectively. The rapid and effective larvicidal activity of these three oils led us to consider these results to be promising, also considering the possibility of local cultivation of these plants in tropical and subtropical areas and the simple technology for their large-scale preparation and production. Further studies are needed to evaluate the individual components and their activity as larvicides.